2019
DOI: 10.1021/acschembio.9b00857
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Proteomic Studies of Human Pyridoxal 5′-Phosphate-Binding Protein (PLPBP)

Abstract: The pyridoxal 5′-phosphate-binding protein (PLPBP) is an evolutionarily conserved protein linked to pyridoxal 5′-phosphate-binding. Although mutations in PLPBP were shown to cause vitamin B6-dependent epilepsy, its cellular role and function remain elusive. We here report a detailed biochemical investigation of human PLPBP and its epilepsy-causing mutants by evaluating stability, cofactor binding, and oligomerization. In this context, chemical cross-linking combined with mass spectrometry unraveled an unexpect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…While all available crystal structures are consistent with PLPBP family members being monomers, size-exclusion chromatography of human PLPHP, performed in two different studies [ 23 , 36 ] revealed a second peak corresponding to dimers. In [ 23 ], the minor peak was shown to depend on disulfide bridges, a result interpreted as PLPHP being mainly monomeric with the possibility of stable dimerization via the formation of a disulfide bridge between exposed cysteines.…”
Section: Structural and Functional Features Of Plpbpsmentioning
confidence: 75%
See 4 more Smart Citations
“…While all available crystal structures are consistent with PLPBP family members being monomers, size-exclusion chromatography of human PLPHP, performed in two different studies [ 23 , 36 ] revealed a second peak corresponding to dimers. In [ 23 ], the minor peak was shown to depend on disulfide bridges, a result interpreted as PLPHP being mainly monomeric with the possibility of stable dimerization via the formation of a disulfide bridge between exposed cysteines.…”
Section: Structural and Functional Features Of Plpbpsmentioning
confidence: 75%
“…Consistent with this, human mutation Tyr69Cys increased dimer formation ( Table 2 ). However, Fux and Sieber [ 36 ] challenged this view, reporting that their PLPHP preparation was predominantly dimeric even under reducing conditions [ 36 ]. They also suggested that discrepancies with the previous work may be due to differences in expression strains or purification strategies.…”
Section: Structural and Functional Features Of Plpbpsmentioning
confidence: 99%
See 3 more Smart Citations